(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In earthquake prone zones the structures are designed to withstand seismic or lateral forces along with the gravity loads. In that respect shear wall system, bracing system, diagrid etc., have been suggested over a period of time. This study observed the combined performance of shear wall and RCC bracing system, and also the effect of their relative position in high rise commercial building (G+10).The study aimed the comparison of performance of shear wall and RCC bracing system in high rise commercial buildings under seismic loading. The total of 6 structural configurations viz., Moment resisting frame (Model 1), MRF stiffened with RCC bracing system (Model 2), MRF stiffened with shear wall system (Model 3), MRF stiffened with both shear wall and RCC bracing system (Model 4A, Model 4B, and Model 4C – Based on different relative location of shear wall and RCC bracing system) were modelled and then analysed. Analysis has been done in accordance with 1893:2002 using STAAD Pro V8i software. The post analysis results concluded that The bracing system improves not only the stiffness and strength capacity but also the displacement capacity of the structure. And in model 4( RCC X-bracing system is placed in similar way as shear wall at corner 2 and 3) is more efficient, safe and economical in earthquake as compared to other analysed models.